Sexual Harassment in Transit Environments among College Students in the #MeToo Era: Reporting Evidence from Six Continents - Ceccato, Vania (American journal of criminal justice, 2021)
Evaluating patterns of sexual violence against young people across the world in the era of the #MeToo movement presents great opportunities for research and practice but also challenges. The aim of this article is to critically assess an internet-based methodology employed in a comparative study conducted with university students in 18 different cities, in six continents. While our main purpose is to examine the methodological aspects of this study, the article also presents briefly its major findings and discusses compiled recommendations to curb sexual violence in some of the most important transit systems in the world. Findings show that sexual violence in transit environments is a common occurrence globally, is highly underreported, and ranges considerably from one city to the other, and between gender groups. Lessons from this study suggest that it is crucial to use identical research tools and choose partners who can ensure that research tasks are undertaken on time, ethically, and with good care for the quality of data and the research process. To curb sexual violence on transit, actions tailored to local contexts are necessary, but as underreporting of harassment is prevalent in all contexts, one global need is initiatives that facilitate incident reporting.